The Use of SPSS to Analyze the Relationship between Working Capital Management and Profitability - Budi Santoso, Halim (Proceedings of KNASTIK, 2012)
Profit maximization is one of the shareholders’ goals from some firms’ investments. Byinvesting some of their money, investors want big returns of their investment. Thecompany can maximize its profit through a well management of its assets and use itsassets well in order to generate revenue. In this article, we test the relationship betweenworking capital management and profitability. We analyze and run multiple linearregressions to test financial statements from Indonesia listed companies. The test isdone using Statistical Package for the Social Sciences (SPSS) Software. The resultsshow that Cash Conversion Cycle has significant positive relationship with return onassets. The same direction with Cash Conversion Cycle, Net Trade Cycle also haspositive relationship with return on assets. Positive significant relationship is alsofound in the relationship between return on assets and firm size. In contrast, debt ratiohas negative significant relationship over return on assets. It is also concluded thatSPSS can be used to analyze the relationship between working capital management andprofitability. Profit maximization can be reached through high Cash Conversion Cycleand Net Trade Cycle, as indicators for Working Capital Management.